O Fundo Amazônia e o desenvolvimento local sustentável : o caso da cooperativa de hortifrutigranjeiros de Boa Vista, Roraima - Eula, María Julieta (2017)
The main objective of this Master dissertation is to analyze the environmental public policy of the federal government of Brazil and the international cooperation, instrumented by the Amazon Fund, which is a pioneering experience of the proposed mechanism within the UN framework to reduce emissions caused by deforestation and forest degradation with sustainable management of the forest (REDD +). The Fund's influence on the local sustainable development of the Municipality of Boa Vista, Roraima, Brazil, through the Cooperativa dos Hortifrutigranjeros de Boa Vista - Coophorta, which manages an Amazon Fund Project from the first half of 2013 until the first half of 2015. This Type of action of environmental policy of the Brazilian federal State is inserted in the International Regime of the Environment context, a kind of domestic unfolding of the guidelines of the Convention of Biological Diversity and the United Nations Framework Convention on Climate Change of the United Nations. Since 1992, after the Earth Convention in Rio de Janeiro, the Brazilian public policies and planning for the Amazon region has as the explicit objective to achieve sustainable development based on the ideology of sustainability as the international standard of the countries to develop. The research´s methodology is deductive. It was used comparative and historical methods for reach the objectives. The first chapter discusses sustainable local development concept and the history of development concept. The second chapter shows the relationship between Brazilian environmental public policy and the ideology of sustainability. The third chapter reviews the information contained in the Coophorta Project n. 12.426. Last chapter treats about the Amazon Fund origin, its international partners, its governance and donated resources that gave support projects financed too. The FA presents itself as a pioneer program of Brazilian REDD+ and it constitutes innovative experience to promote the sustainable management of the forest. The research conclusion point out that the studied Coophorta is an instrument of endogenous development allocated in the Boa Vista city and donated resources from the partnership Amazon Fund have a positive influence on the develpoment process. However, the Coophorta and FA reports present insufficient and inconsistent information to measure the impact of the investment. This research is also an opportunity to study the intervention of the Amazon Fund in the Brazilian Amazon.